Design And Development of Web-Based Virtual Reality Learning Environment for Ergonomics Subject - Teoh, Isabelle Ee Hsia (Universiti Malaysia Sarawak, (UNIMAS), 2001)
The higher education sector is changing rapidly mainly as a consequence of its response to the various pressures associated with widening access, commercialism and developments in information and communication technologies. Some learners tend to have boredom and form no interest in learning new concept through the Internet. They have faced some problem in visualizing and understanding new concept learnt through the Internet. The objective of this research is to design and develop a web-based virtual reality learning environment for ergonomics class. This research compares the effectiveness of learning through traditional teaching and learning through web-based virtual reality learning environment for ergonomics class. The traditional teaching model adopted in this research uses chalk and blackboard as the medium of teaching. This research is also aimed to design and develop an interactive learning environment and employ an user friendly interface of the web-based virtual reality learning environment. A conceptual framework is designed in order to classify the independent and dependent variables in this research, and various software is used to develop the system. From the finding. learning the interesting ergonomics subject through web-based virtual reality learning environment is more effective than learning through Traditional learning. This research also determines the web-based virtual reality learning environment is an interactive learning environment and has met the criteria of user friendly interface. To conclude, this web-based virtual reality learning environment is more effective because it is interactive and has met the user friendly interface. This web-based virtual reality learning environment can be the supplement for traditional teaching and will change the role of learners from those who are passive to become participants in learning environment. Moreover, this system creates a long life opportunity for those who are unable to attach physical campus and create conducive learning environment. The web-based learning environment is well suited because many learning institutions now espouse a turn to student-centered learning. A part from that, learning interesting subject such as ergonomics is necessity and beneficial because it provides a set of conceptual guidepost for adapting work, places, product and services to fit human needs.